PENGARUH E-COMMERCE STRATEGY, SERVICE PERFORMANCE DAN KEPUASAN SEBAGAI MODERATING VARIABLE TERHADAP LOYALITAS NASABAH BANK BRI UNISMA MALANG - Nurus Sofi; Rois Arifin; Ahmad Agus Priyono (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACT The purpose of this research is to know and analyze the influence of E-Commerce strategy, service performance and satisfaction as moderating variable to customer loyalty of Bank BRI Unisma Malang. Partially to customer loyalty of Bank BRI Unisma Malang. The sampling technique using purposive sampling is a technique of determining the sample with certain considerations. Data analysis tool used in this research is Simple Linear Regression Analysis And Moderating Regression Analysis (MRA) Based on the results of this study note that E-Commerce Strategy variables directly affect customer loyalty, Service Performance variables directly affect customer loyalty. While the interaction Variable E-Commerce Strategy and Customer Satisfaction does not directly affect customer loyalty and Service Performance and Customer Satisfaction does not directly affect customer loyalty.Keyword : E-Commerce Strategy, Service Performance, Customer Satisfaction and Customer Loyalty